An essay on private equity: the history and fundamentals of fundraising in Brazil - Ramalho, Caio Cezar Monteiro (2013)
The positive impact of the Private Equity and Venture Capital (PE/VC) investments in the economy and in the capital markets is widely documented in the international literature. In the past 40 years, several authors have investigated the influence this asset class in the creation, development and transformation of thousands of companies worldwide, especially in the United States. However, literature on the determinants of PE/VC fundraising has developed only recently, and their results are far from being unanimous. In Brazil, research about the PE/VC industry is still scarce. Although the local industry has been growing fast since 2006 to achieve US$36.1 billion of committed capital in 2009, there are no studies about which variables drive investor’s capital allocation in this asset class in Brazil. Understand this dynamics is important to the market equilibrium and efficiency. Based on Gompers and Lerner (1998) work about the determinants of this industry in the United States, the present study contributes to the PE/VC literature by: (i) revisiting industry’s beginning in Brazil, and (ii) identifying the variables which are related to the development of the local industry. The results of this work contribute to the PE/VC academic development in Brazil. Moreover, the discussions presented herein may impact some related fields of study, such as Portfolio Management, Corporate Governance, Entrepreneurship, and Strategy. Practitioners may also be interested in the study. The discussion about industry’s history and fundamentals provide investors, entrepreneurs, fund managers and policymakers, among others, a better understanding of how the PE/VC ecosystem works in Brazil.